2015
DOI: 10.1186/s40885-015-0018-5
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces endoplasmic reticulum stress in podocyte, which would be further augmented by PI3-kinase inhibition

Abstract: IntroductionAngiotensin II (Ang II) contributes to the pathological process of vascular structures, including renal glomeruli by hemodynamic and nonhemodynamic direct effects. On renal effects, Ang II plays an important role in the development of proteinuria and glomerulosclerosis by the modification of podocyte molecules and cell survival. In the present study, we investigated the effect of Ang II on endoplasmic reticulum (ER) stress in podocytes.MethodsWe cultured mouse podocytes with increasing doses of Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…ACE2 counterbalances the effects of the classic RAS through conversion of Ang II to Ang‐(1‐7). Ang II has been reported to induce podocyte ERS via GRP78/eIF2α/ATF4/CHOP axis . In the present study, the changes in GRP78/ATF4/CHOP expression in ACE2 KO mice and Ad‐ACE2–treated db/db mice suggested that Ang II and ACE2 induce ERS may through the same pathway.…”
Section: Discussionsupporting
confidence: 58%
“…ACE2 counterbalances the effects of the classic RAS through conversion of Ang II to Ang‐(1‐7). Ang II has been reported to induce podocyte ERS via GRP78/eIF2α/ATF4/CHOP axis . In the present study, the changes in GRP78/ATF4/CHOP expression in ACE2 KO mice and Ad‐ACE2–treated db/db mice suggested that Ang II and ACE2 induce ERS may through the same pathway.…”
Section: Discussionsupporting
confidence: 58%
“…ER stress is common under various pathogenic microenvironments and contributes to progression of various podocyte diseases. Abnormal protein accumulation associated with podocyte-specific ER stress induces structural and functional damage in cells, which in turn leads to apoptosis and severe proteinuria [ 21 23 ]. The ER stress mechanisms underlying the development of podocyte injury by PAN remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, this Ang II/ER stress/SREBP activation needs to be confirmed in experimental animal models to provide stronger evidence. As Ang II might also induce ER stress in podocytes (Ha et al, 2015) and proximal tubular epithelial cells (Wang J. et al, 2015), other studies with these kidney cell subtypes are needed, as well. EGFR may be an important second signal in TGFβ upregulation via activation of the SREBP1 cotranscription factor Sp1.…”
Section: Srebp Induces Tgfβ Transcriptional Activitymentioning
confidence: 99%